2015
DOI: 10.1007/s10493-015-9879-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring and population dynamics of ixodid ticks in Tomsk city (Western Siberia)

Abstract: Monitoring of two tick species (Ixodes persulcatus Schulze 1930 and Ixodes pavlovskyi Pomerantsev) was performed in four city parks of Tomsk, Russia (Camp Garden, University Park, Southern Cemetery, and Polytechnic Stadium) and in a control wild biotope in city environs (Kolarovo) in 2002-2013. Ticks were collected by flagging repeatedly after each 10 ± 1 days, starting from the disappearance of the snow cover till the end of tick activity (April-August). Gradual penetration of both tick species into city park… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
2
7
0
3
Order By: Relevance
“…From the beginning of this century, an increased abundance of I. pavlovskyi ticks has been recorded more northward in Western Siberia in parks and suburban areas of Novosibirsk and Tomsk, large Siberian cities situated in the Western Siberian Plain. In these suburban areas, I. pavlovskyi ticks have become predominant in a number of locations, reaching 82–94% of tick samplings [35, 58, 62, 63]. Ixodes pavlovskyi ticks frequently attack people [1, 64, 65]; however, the role of the tick species in the epidemiology of tick-borne diseases has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…From the beginning of this century, an increased abundance of I. pavlovskyi ticks has been recorded more northward in Western Siberia in parks and suburban areas of Novosibirsk and Tomsk, large Siberian cities situated in the Western Siberian Plain. In these suburban areas, I. pavlovskyi ticks have become predominant in a number of locations, reaching 82–94% of tick samplings [35, 58, 62, 63]. Ixodes pavlovskyi ticks frequently attack people [1, 64, 65]; however, the role of the tick species in the epidemiology of tick-borne diseases has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…При этом исследований, посвященных специфике численности на городской терри-тории, значительно меньше. Так, в г. Томске показана более низкая численность I. persulcatus в парках города по сравнению с пригород-ными лесопарками, что объясняется большей антропогенной нагрузкой на почвенный покров [Романенко, 1999Romanenko, Leonovich, 2015].…”
Section: Discussionunclassified
“…Исследования, посвященные изучению рас-пространения иксодовых клещей на урбанизи-рованных территориях, многочисленны [Сапе-гина и др., 1985;Романенко, 2005Uspensky, 2008Uspensky, , 2014Foldvari et al, 2011;Greenfield, 2011;Tretyakov et al, 2012;Jennett et al, 2013;Romanenko, Leonovich, 2015], и их актуаль-ность во многом определяется возможностью длительного устойчивого существования по-пуляции клещей в условиях большого города. В настоящее время наиболее приоритетным направлением становится сравнительный ана-лиз зараженности клещей инфекциями город-ских и пригородных (естественных) биотопов [Москвитина и др., 2008;Hamel et al, 2013;Hornok et al, 2014;Rizzoli et al, 2014].…”
unclassified
“…Leg segments were cut right on the walkway with the use of a miniature scalpel (blade width about 0.5 mm) under a control of a head magnifying glass (×10), at a background of white sheet of a paper notebook. The same glass allowed us to determine species belonging; after several years of experience, when field determination was afterwards checked in laboratory (Romanenko and Leonovich, 2015), revealing differences between I. persulcatus and I. pavlovskyi became evidently clear.…”
Section: Methodsmentioning
confidence: 99%
“…Long-term monitoring of ticks in city parks and suburbs of the city of Tomsk had demonstrated that in 2002-2014, both tick species had gradually penetrated city parks. In forests surrounding the city, I. persulcatus formed about 95% of tick population, whereas in urban biotopes I. pavlovskyi became the dominant species (Romanenko and Leonovich, 2015). The virus of the tick-borne encephalitis (TBE) was isolated from ticks of both species that had attached to humans during visiting city parks of Tomsk and forest-parks situated in city outskirts.…”
Section: Introductionmentioning
confidence: 99%